THE USE OF METHODOLOGICAL TECHNOLOGIES OF TEACHING IN HISTORY LESSONS - Sharofiddinov Rivojiddin Shamsiddinovich (Modern American Journals, 2025)
With a theoretical and practical approach to educational technologies and methods, educational technologies of the use of technology, methods and tools of teaching the use of methods of teaching history, to convey the essence of the subject of history to students, to increase students' knowledge based on the goals and objectives of science, to enlighten the secrets of science. This scientific article differs from the previous educational literature in that it is enriched with the generally recognized results of research conducted during the years of independence, introduction of innovations in the educational process.
Keywords: Reproductive, psychodrama, sociodrama, technological characterization, taxonomy, module, individual approach, skills, methodology, physical teaching, imitation games, didactics.